The Effect of Discovery Learning Model Using Canva and I-Spring Suite on Student Learning Outcomes and Motivation in Stoichiometry Material - Yohana Fransiska Sitanggang; Ratna Sari Dewi (Jurnal Pendidikan Kreatif, 2025)
The aim of this research is to determine whether there is an influence and correlation between the Discovery Learning model using Canva and I-Spring Suite on learning outcomes and student motivation in stoichiometry material. This research uses a quasi-experiment with a quantitative approach. The analysis technique used is the two-party t test. From the results of data analysis on learning outcomes and student motivation, it was found that there was an influence of the Discovery Learning model using Canva and I-Spring suite on student learning outcomes and motivation on stoichiometry material. Based on the data obtained, namely tcount>ttable on student learning outcomes (2.93>1.66), and on student motivation (2.48>1.66). Based on the data, it is known that there is an increase in learning outcomes in each class when implementing learning models and media (67.15% and 63.5%). In terms of student motivation, it can be seen that the percentage of student motivation is 74.4% for experimental class I and 71.3% for experimental class II. The correlation of increasing learning outcomes and student motivation in experimental class I and experimental class II is quite low, namely 0.0116 and 0.0114.